Proteomic profiling during atherosclerosis progression: Effect of nebivolol treatment - ÖZBEN SADIÇ, BESTE (SPRINGER, 2009)
There is a great need for the identification of biomarkers for the early diagnosis of atherosclerosis and the agents to prevent its progression. The aim of this study was to explore the effect of 24 week of nebivolol (a third-generation vasodilatory beta-blocker) treatment on serum protein profiles in Apo E-/- mice during atherosclerosis progression. Nebivolol treated and non-treated (the control group) groups consisted of 10 genetically modified homozygous Apo E-/- mice. Proteomic analyses were performed using surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF MS) in the serum samples from the nebivolol treated and non-treated Apo E-/- mice. The protein profiles obtained using three different chips, CM10 (weak cation-exchange), H50 (reverse phase), and IMAC30-Cu2+ (immobilized metal affinity capture) were statistically analyzed using the ProteinChip data manager 3.0 program. At the end of 24 week of nebivolol-treatment period, a total of 662 protein/peptide clustering peaks were detected using 12 different conditions and reading with high and low intensity laser energy. The highest total number of protein/peptide clusters was found on H50 chip array. The peak intensities of 95 of the 662 protein/peptide clusters were significantly different in the nebivolol-treated atherosclerotic group in comparison to the non-treated control mice groups (P < 0.05). Forty-three protein/peptides were up-regulated (high signal intensity) while 52 protein/peptides had lower signal intensity (down-regulated) in the nebivolol-treated atherosclerotic group. The proteomic profiles of nebivolol-treated Apo E-/- mice were different than the control group indicating a potential role of nebivolol in atherosclerosis. Our study contributes to understand the efficacy of nebivolol on serum protein/peptide profiles during atherosclerosis development.
Keywords: Atherosclerosis; Proteomics; Nebivolol; SELDI-TOF MS; Apo E knock-out mice; E-O MICE; SMOOTH-MUSCLE; MASS-SPECTROMETRY; OXIDATIVE STRESS; GENE-EXPRESSION; NITRIC-OXIDE; APOLIPOPROTEIN; BIOMARKERS; PROLIFERATION; LESION